2017
DOI: 10.5606/archrheumatol.2017.6273
|View full text |Cite
|
Sign up to set email alerts
|

Beta-2 Microglobulin in Whole Unstimulated Saliva Can Effectively Distinguish Between Sjögren’s Syndrome and Non-Autoimmune Sicca Symptoms

Abstract: Objectives: This study aims to describe salivary beta-2 microglobulin (sB2M) levels in our setting and to assess the performance of sB2M for the diagnosis of Sjögren's syndrome (SS). Patients and methods:This cross-sectional, comparative study included 192 SS patients (2 males, 190 females; mean age 53.1 years; range 23 to 84 years) and 64 healthy controls (1 male, 63 females; mean age 46.9 years; range 21 to 82 years). Patients were divided into three groups as those with primary SS, secondary SS, and sicca n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In a multicentric study carried out by Gottenberg et al with primary Sjögren's syndrome patients at 15 centers, it was demonstrated that increased β2M levels were associated with increased EULAR Sjögren's Syndrome Disease Activity Index (p < 0.001) [26]. A study conducted with 192 Sjögren's syndrome patients, it was shown that the unstimulated whole salivary β2M levels in both primary and secondary Sjögren's syndrome patients were significantly higher than both the healthy control group and the non-Sjögren sicca symptom group [27].…”
Section: Discussionmentioning
confidence: 96%
“…In a multicentric study carried out by Gottenberg et al with primary Sjögren's syndrome patients at 15 centers, it was demonstrated that increased β2M levels were associated with increased EULAR Sjögren's Syndrome Disease Activity Index (p < 0.001) [26]. A study conducted with 192 Sjögren's syndrome patients, it was shown that the unstimulated whole salivary β2M levels in both primary and secondary Sjögren's syndrome patients were significantly higher than both the healthy control group and the non-Sjögren sicca symptom group [27].…”
Section: Discussionmentioning
confidence: 96%